2023
DOI: 10.1021/acs.jafc.3c05217
|View full text |Cite
|
Sign up to set email alerts
|

Natural Occurrence of Nitrite-Related Compounds in Malt and Beer

Michaela Malečková,
Tomáš Vrzal,
Tomáš Vaško
et al.

Abstract: Despite sufficient control of volatile N-nitrosamines in foods and beverages, little attention remained on nonvolatile nitroso compounds, which are mostly unknown and relative to nitrite reactions. In a recent study, new compounds related to reactions of nitrite in beer were pyruvic acid oxime, 4-nitrosophenol, 4-cyanophenol, N-nitrosoproline ethyl ester, nitrosoguaiacol, and 2-methoxy-5-nitrophenol, as well as the already known N-nitrosoproline. The present study is intended to observe their natural occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Figure 4 shows the FTIR spectra of No NA/SDA, NaCl, GA, and T samples of ME-AgNPs (Figures 4a, 4b, 4c and 4d, respectively). Figure 4a peaks correspond to main peaks around 2926, 1646, 1456, 1338, 1240, 1206, 1152, 1077, and 993 cm −1 and a prominent peak area between 925 and 400 cm −1 previously described for ME (Figure 3), which indicates the presence of ME biomolecules acting as stabilizing agents on the surface of these AgNPs [48,49]. In the case of NaCl/ME-AgNPs (Figure 4b), besides the peaks corresponding to Figure 4 shows the FTIR spectra of No NA/SDA, NaCl, GA, and T samples of ME-AgNPs (Figures 4a, 4b, 4c and 4d, respectively).…”
Section: Ftir Analysissupporting
confidence: 65%
See 1 more Smart Citation
“…Figure 4 shows the FTIR spectra of No NA/SDA, NaCl, GA, and T samples of ME-AgNPs (Figures 4a, 4b, 4c and 4d, respectively). Figure 4a peaks correspond to main peaks around 2926, 1646, 1456, 1338, 1240, 1206, 1152, 1077, and 993 cm −1 and a prominent peak area between 925 and 400 cm −1 previously described for ME (Figure 3), which indicates the presence of ME biomolecules acting as stabilizing agents on the surface of these AgNPs [48,49]. In the case of NaCl/ME-AgNPs (Figure 4b), besides the peaks corresponding to Figure 4 shows the FTIR spectra of No NA/SDA, NaCl, GA, and T samples of ME-AgNPs (Figures 4a, 4b, 4c and 4d, respectively).…”
Section: Ftir Analysissupporting
confidence: 65%
“…Considering that it has been reported that malt has around 5042 compounds which include amines, alcohols, carboxylic acids, terpenes, etc. [48], and also nitroso compounds such as N-nitrosodimethylamine have been found in malt [49], the detection of the signals of these functional groups on the surface of ME-AgNPs was expected. Figure 4 shows the FTIR spectra of No NA/SDA, NaCl, GA, and T samples of ME-AgNPs (Figures 4a, 4b, 4c and 4d, respectively).…”
Section: Ftir Analysismentioning
confidence: 92%